Pengaruh Faktor Religiusitas terhadap Keputusan Nasabah Memilih Produk Tabungan pada PT. Bank BNI Syariah Cabang Makassar - Nurdiansyah, Nurdiansyah; Jannah, Fachriyahthul; Yulianadewi, Ina (Patria Artha Management Journal, 2023)
The Influence of Religiosity Factors on Customers' Decisions to Save at PT. Bank BNI Syariah Branch Makassar. The purpose of this study was to analyze the effect of religiosity on the decision to save at PT. Bank BNI Syariah Branch Makassar. The analytical method used in this research is descriptive quantitative and the analysis using simple regression and use an SPSS application assistance. The results of the analysis, that the religiosity factor has a positive and significant effect on the decision to save at PT. Bank BNI Syariah Branch Makassar.